Sulfonated graphene oxide‐doped proton conductive membranes based on polymer blends of highly sulfonated poly(ether ether ketone) and sulfonated polybenzimidazole. Issue 37 (10th June 2018) - Gao, Shuitao; Chen, Xin; Xu, Hulin; Luo, Tianwei; Ouadah, Amina; Fang, Zhou; Li, Yang; Wang, Run; Jing, Chaojun; Zhu, Changjin
ABSTRACT: Simultaneously improving the proton conductivity and mechanical properties of a polymer electrolyte membrane is a considerable challenge in commercializing proton exchange membrane fuel cells. In response, we prepared a new series of miscible polymer blends and thus the corresponding crosslinked membranes based on highly sulfonated poly(ether ether ketone) and sulfonated polybenzimidazole. The blended membranes showed more compact structures, due to the acid‐base interactions between the two constituents, and improved mechanical and morphological properties. Further efforts by doping sulfonated graphene oxide (s‐GO) forming composite membranes led to not only significantly elevated proton conductivity and electrochemical performance, but also better mechanical properties. Notably, the composite membrane with the filler content of 15 wt % exhibited a proton conductivity of 0.217 S cm −1 at 80 °C, and its maximum power density tested by the H2 /air single PEMFC cell at room temperature reached 171 mW cm −2, almost two and half folds compared with that of the native membrane. As a result, these polymeric membranes provided new options as proton exchange membranes for fuel‐cell applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46547. Abstract :